(3GddDdDI GdeVjI aj GdYed HGdfSHI GdSJjfjIs - (3CHi GdaVGFd YR GdOjf YHO GdYRjR Hf eMeO Gd haGFi GdehbJs; (3YHO GdYRjR Hf eMeO GdhaGFj GdehbJ, YR GdOjf CHj GdaVGFd,J (B876 (3g` s
(3ChdgG (B:s
(3bGd GdhaGFi hHYO , agPg QSGdI dWjaI ai eYQaI MSGH GdOQL hGdObGFb hSeJjgG GddDdDI GdeVjI ai GdYed HGdfSHI GdSJjfjI s
(3BNQgG (B:s
(3hEf TFJ aGVQH GdLPQ ai faSg hRO HbjJg Ydi MGUd GdVQH hGfXQ aEf JSGhi GdeLPhQ agh UMjM , hEdG aCYOg hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3HBNQgG LOhd LfS NGQL GdVQH hLOhd LfS NGQL GdbSeIs
(3GdfSNI ebGHdIs
(3ai GdeYgO fSNI CNQi HQbe (B176 (3adc s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3Gdadcs